Application of the Project-Based Learning Model to Increase Students Interest in Learning the Material Between Colonialism and Imperialism in Class XI - 8 SMA Negeri 5 Medan - Malau, Brata Eka Riski; Sumatri, Pulung; Nasution, Sovianur (LPPPI Publishing, 2024)
This research aims to increase the learning interest of students XI - 8 SMA Negeri 5 Medan. This research is Collaborative Class Action Research, carried out in 2 cycles. The sample in this research were students in class XI – 8 odd semester 2024/2025 academic year with 35 students. The data collection techniques used are Observation and documentation. Based on the research results in cycles 1 and 2, students can complete the project assignments given and present them. So, it can be concluded that there was an increase in students' interest in learning from Cycle I and Cycle II by 20% after implementing the Project Learning learning model on the material Between Colonialism and Imperialism.